Determinants of gestational weight gain with special respect to maternal stature height and its consequences for newborn vital parameters - Kirchengast, Sylvia; Hartmann, Beda (Anthropological Review, 2013)
An appropriate gestational weight gain is an essential factor of female reproductive success because gestational weight gain influences newborn size but also maternal and infant morbidity and mortality. This paper aims to analyze the impact of maternal somatic factors, first of all maternal stature height, on gestational weight gain. Additionally the effect of gestational weight gain and other maternal somatic factors on newborn size was tested. In the present study the data of 12,661 term birth which have taken place in Vienna, Austria were analyzed. Maternal and newborn somatometric features such as prepregnancy weight status, maternal stature height, birth weight, birth length and head circumference were included. Nearly 65% of the women gained appropriate weight during pregnancy. About 20% showed an excessive, less than 15% an inappropriate gestational weight gain. Gestational weight gain was influenced significantly by prepregnancy weight status, maternal stature height, maternal age, but also nicotine consumption during pregnancy. A significant association between gestational weight gain and newborn somatometrics could be stated. It could be shown that gestational weight gain is influenced by several maternal somatic but also behavioral factors. Newborn size is associated with gestational weight gain.